A short history of global evangelicalism - Hutchinson, Mark (Cambridge University Press, 2012)
"This book offers an authoritative overview of the history of evangelicalism as a global movement, from its origins in Europe and North America in the first half of the eighteenth century to its present-day dynamic growth in Africa, Asia, Latin America, and Oceania. Starting with a definition of the movement within the context of the history of Protestantism, it follows the history of evangelicalism from its early North Atlantic revivals to the great expansion in the Victorian era, through to its fracturing and reorientation in response to the stresses of modernity and total war in the late nineteenth and early twentieth centuries. It describes the movement's indigenization and expansion toward becoming a multicentered and diverse movement at home in the non-Western world that nevertheless retains continuity with its historic roots. The book concludes with an analysis of contemporary worldwide evangelicalism's current trajectory and the movement's adaptability to changing historical and geographical circumstances"--